Ethical responsibilities toward wildlife - Rolston, Holmes, 1932-2025, author; American Veterinary Medical Association, publisher (Colorado State University. Libraries, 1992)
Save the whales! Let the bison drown! Let the lame deer suffer! Leave wounded deer to the coyotes! Let the blinded bighorns starve! Treat the bighorns with lung worm! Rescue the sow grizzly! Shoot the feral goats! Sterilize the mustangs! Restore the wolves! Respect wild life! Compassion is not the only consideration in an ethic, and in environmental ethics it plays a different role than in a humanist ethics. To intervene artificially in the processes of natural selection is not to do wild animals any benefit at the level of the good of the kind, although it would benefit an individual. However, intervention is warranted if humans have caused the suffering or threatened the species.
Originally a keynote address, "Ethical Responsibilities toward Wildlife," at the American Veterinary Medical Association Forum on "The Veterinarian's Role in the Welfare of Wildlife," Palmer House, Chicago, IL, November 7, 1991.
Keywords: let nature take its course; bison; deer; suffering in wild animals; wolves; grizzly bears; compassion; medical intervention in wildlife